IMMU-49. CYTOTOXIC T CELLS AND THEIR ACTIVATION STATUS ARE INDEPENDENT PROGNOSTIC MARKERS IN MENINGIOMAS. (5th November 2018) - Herold-Mende, Christel; Rapp, Carmen; Jungk, Christine; Sahm, Felix; Lamszus, Katrin; Ketter, Ralf; Löhr, Mario; Senft, Christian; Westphal, Manfred; Deimling, Andreas von; Unterberg, Andreas; Simon, Matthias
Abstract: Although clinically aggressive meningiomas (MGMs) are rare tumors, more effective therapies are urgently needed. As a prerequisite for successful immunotherapy we determined the infiltration and activation status of T cells in primary (p-) and recurrent (r-) MGMs and their impact on survival. Presence of tumor-infiltrating lymphocytes (TILs) was assessed in a large, clinically well-annotated study sample of 202 cases (n=123 pMGMs, and n=79 rMGMs) with a substantial proportion of higher-grade MGMs (n=43 WHO°I, n=97 WHO°II, n=62 WHO°III). TIL quantification was performed by a semi-automated analysis on whole tissue sections stained by multi-color immunofluorescence for CD3, CD8, FOXP3, and PD-1. Ranging from 0.01–24.88 %, median T cell infiltration accounted for 0.59 TILs per total cell count (TCC). Although there were no significant changes for the proportion of helper and cytotoxic T cells in pMGM of different WHO grades, higher numbers of cytotoxic T cells were associated with an improved progression-free survival (PFS) independent of prognostic confounders. rMGM were characterized by significantly lower numbers of TILs in general (median: 0.33 % per TCC), helper and cytotoxic T cells and a significant increase of regulatory T cells. As for the activation of TILs, about one third expressed the immune checkpoint molecule PD-1 and predominantly were CD8-positive. We observed a significant WHO-dependent decrease of PD-1 + /CD8 + TILs which in univariate and multivariate analyses were associated with a poorer PFS. In line with these findings proportions of PD-1 + /CD8 + TILs were significantly lower in rMGM arguing for PD-1 as an activation rather than an exhaustion marker. In summary, we were able to identify intratumoral cytotoxic TILs as well as of PD-1-expressing cytotoxic TILs as novel and easy applicable biomarkers for a better survival, which might facilitate the selection of patients who could benefit from immunotherapeutic approaches and mandates for an intervention in primary rather than recurrent tumors.